Photocatalytic Hydrogen Evolution of TiZrNbHfTaOx High-Entropy Oxide Synthesized by Mechano-Thermal Method - Guler, Omer; Boyrazli, Mustafa; Albayrak, Muhammet Gokhan; Guler, Seval Hale; Ishihara, Tatsumi; Edalati, Kaveh (Mdpi, 2024)
One of the most promising solutions to slow down CO2 emissions is the use of photocatalysis to produce hydrogen as a clean fuel. However, the efficiency of the photocatalysts is not at the desired level, and they usually need precious metal co-catalysts for reactions. In this study, to achieve efficient photocatalytic hydrogen production, a high-entropy oxide was synthesized by a mechano-thermal method. The synthesized high-entropy oxide had a bandgap of 2.45 eV, which coincided with both UV and visible light regions. The material could successfully produce hydrogen from water under light, but the main difference to conventional photocatalysts was that the photocatalysis proceeded without a co-catalyst addition. Hydrogen production increased with increasing time, and at the end of the 3 h period, 134.76 mu mol/m2 h of hydrogen was produced. These findings not only introduce a new method for producing high-entropy photocatalysts but also confirm the high potential of high-entropy photocatalysts for hydrogen production without the need for precious metal co-catalysts.
Keywords: high-entropy alloys; high-entropy oxides; photocatalysis; mechano-thermal process; hydrogen production